Gender-Based Violence: Lived experiences of female students at the University of the Witwatersrand - Kgolane, Serole Joy (University of the Witwatersrand, Johannesburg, 2023)
This research aimed to explore experiences of Gender based violence (GBV) among female students at the University of the Witwatersrand. It sought to ascertain how these experiences unfolded as well as the impact they have had on the students. Intersectionality theory was applied as the theoretical framework to observe the impact of overlapping identities on the students’ experiences of GBV. The study consisted of seven female participants who were selected using a volunteer sampling method. Interpretive phenomenological analysis (IPA) was used to analyse the transcribed interviews and derive themes from the collected data. Four themes in total were identified: power relations, internal experience, normalization of GBV, and help-seeking. The objectives of the study were used to guide the analysis of the themes. The findings showed that students face stalking, verbal abuse, emotional abuse, physical abuse, and sexual abuse perpetrated mostly by fellow male students. Moreover, influences of hegemonic masculinity and gendered power imbalances played a role in the perpetration of violence against the female students. Furthermore, the findings indicate that these experiences had adverse effects on the mental well-being of the students and led the students to adopt various coping strategies while often failing to engage in help-seeking behaviour.
A research project submitted in partial fulfilment of the requirements for the degree of Master of Arts by Coursework and Research Report in the field of Master of Arts: Community-based Counselling, in the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Gender-based violence; Intimate partner violence; Female students; University; UCTD; Community-based Counselling; SDG-5: Gender equality